Exploration of Ion Channels in Mycobacterium tuberculosis: Implication on Drug Discovery and Potent Drug Targets Against Tuberculosis - Dwivedi, Manish (Current Chemical Biology, 2020)
Scientific interest in mycobacteria has been sparked by the medical importance of Mycobacterium tuberculosis (Mtb) that is known to cause severe diseases in mammals, i.e. tuberculosis and by properties that distinguish them from other microorganisms which are notoriously difficult to treat. The treatment of their infections is difficult because mycobacteria fortify themselves with a thick impermeable cell envelope. Channel and transporter proteins are among the crucial adaptations of Mycobacterium that facilitate their strength to combat against host immune system and anti-tuberculosis drugs. In previous studies, it was investigated that some of the channel proteins contribute to the overall antibiotic resistance in Mtb. Moreover, in some of the cases, membrane proteins were found responsible for virulence of these pathogens. Given the ability of M. tuberculosis to survive as an intracellular pathogen and its inclination to develop resistance to the prevailing anti-tuberculosis drugs, its treatment requires new approaches and optimization of anti-TB drugs and investigation of new targets are needed for their potential in clinical usage. Therefore, it is imperative to investigate the survival of Mtb. in stressed conditions with different behavior of particular channel/ transporter proteins. Comprehensive understanding of channel proteins and their mechanism will provide us direction to find out preventive measures against the emergence of resistance and reduce the duration of the treatment, eventually leading to plausible eradication of tuberculosis.
Keywords: Mycobacterium